Authoritarian Neoliberal Statecraft and the Political Economy of Mis/Disinformation: Resituating Western-Centric Debates in a Vietnamese Context - Yến-Khanh, N; Phelan, S (Center for Information, Technology, and Public Life at the University of North Carolina at Chapel Hill., 2023)
Academic and popular discussions of misinformation, disinformation, and “fake news” have prioritized the concerns of Western liberal democracies. In the rather different context of Vietnam, we highlight how the interplay of authoritarian state logics, corporate interests, weak journalism, and repressed civil society culture explains the way mis/disinformation manifests in Vietnamese news media. We argue that the ongoing need to de-Westernize media and communication studies must be part of any satisfactory answer to the question of “what comes after disinformation studies.”